157k views
2 votes
What is the answer (algebra)
-(4x + 3x) = 10x - 5

1 Answer

5 votes

Explanation:

-(4x + 3x) = 10x - 5

We would have to multiply the -1 by the 4x and the 3x which is in the bracket.

Though there is no 1 behind the bracket but, behind any bracket there is 1 there even though it's ignored.

So when we multiply -1 by 4x we are going to get;

-4x

And when we multiply -1 by 3x It's going to be;

-3x

We have -3 and -4 because whenever we multiply any positive and negative number the product is negative.

So;

-4x - 3x = 10x - 5

So now, we group like terms;

- 4x - 3x - 10x = -5

So now that we have grouped, we have to add the negative numbers even though there is no addition sign there we would have to add

-17x = -5

So now we divide both sides by;

-17

Which is going to be;

x=


(5)/(17)

User LenW
by
6.2k points